Optimizing Resilience Using Network Structural Parameters for Reconfigurable Supply Chains - Choudhary, Hrishikesh; Pattanaik, Laxmi Narayan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
Resilience of supply chains is considered a desirable feature owing to the disruptions and uncertainties at various levels and operations. Several strategies to enhance resilience are practiced with supply chain network designs, multisource decisions, inventory and capacity buffers, near-shoring, etc. In the present work, the assessment and optimization of resilience under reconfigurations of a generic supply chain is conducted utilizing network structural parameters like size, density, clustering coefficient, centrality, and effective arc length. The effect of reconfigurations on resilience is analyzed separately for the upstream and downstream of the supply chain since the practical implementation on each side is different. A bi-objective optimization model is developed for maximizing resilience and minimizing transportation cost, considering several potential configurations using the network structural parameters. Pareto optimal solutions are found through NSGA II for model data sets of these combinatorial optimization problems representing upstream and downstream separately.